Melanoma in horses: Current perspectives. (17th January 2012) - Moore, J. S.; Shaw, C.; Shaw, E.; Buechner‐Maxwell, V.; Scarratt, W. K.; Crisman, M.; Furr, M.; Robertson, J.
Summary Debate surrounding the nature of equine melanoma has resulted in an underestimation of its life‐threatening potential. Contrary to popular dogma, the variable, often slow, rate of growth commonly associated with equine melanoma does not warrant benign classification. Equine melanoma is a malignant neoplasm with the capacity for local invasion and metastasis. A classification scheme was proposed in 1995, but this does not address the progressive nature of equine malignant melanoma (EMM). Additionally, frustration with conflicting therapeutic recommendations has led many practitioners to inappropriately advocate benign neglect. This article addresses the need for a clinically applicable, standardised classification system, provides a review of current therapies and recommendations for equine practitioners, and comments on the future directions of EMM research.